THE INFLUENCE OF DIGITAL MARKETING AND ADVERTISING EFFECTIVENESS ON GEN Z BUYING INTEREST IN MARKETPLACES IN THE SPECIAL REGION OF YOGYAKARTA - Vera Desy Nurmalia; Arifah Fajar Nur Qolbi (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This study aims to analyze the effect digital marketing and advertising effectiveness on gen z buying interest in marketplace in the Special Region of Yogyakarta. This research uses quantitative research methods. The sampling technique used wae purposive sampling with a total of 100 respondents. Primary data used in this study are perceptions obtained from quentionnaires distributed to gen z in the Special Region of Yogyakarta. The test carried out in this study are descriptive analysis, instrument test (validity test and reliability test), classical assumption test (normality, linearity, multicollinearity and heteroscedacity), hypothesis testing (t test and f test), multiple linear regression analysis and coefficient of determination (Adjusted R2). The results of this study indicate that : 1) digital marketing has a positive and significant effect on purchase intention. 2) advertising effectiveness has a positive and significant effect on buying interest. 3) digital marketing and advertising effectiveness simultaneously affect buying interest.